Fish biodiversity sampling in stream ecosystems: a process for evaluating the appropriate types and amount of gear. Issue 3 (10th December 2013) - Smith, Joseph M.; Wells, Sarah P.; Mather, Martha E.; Muth, Robert M.
ABSTRACT Because human impacts and climate change threaten aquatic ecosystems, a need exists to quantify catchment‐scale biodiversity patterns and identify conservation actions that can mitigate adverse human impacts on aquatic biota. Whereas many traditional aquatic resource questions can be answered by repeatedly sampling a few target species with limited types of gear in the same habitats, sampling fish biodiversity patterns at larger scales requires a different approach. Researchers and managers need to determine the types of sampling gear and amount of effort that provide a representative estimate of biodiversity in a range of habitats across a catchment. Using a randomized block design within a 90‐m stream reach that contained the same habitats as the scientific study area, fish assemblages were compared using three different types of gear (minnow traps, backpack electrofishing, and hoop nets) at three levels of effort (one, two, and three mixed‐gear units) over four replicate days. A mixture of gear types best quantified fish assemblages. A combination of 10 minnow traps, 20‐m of backpack electrofishing, and two hoop nets caught the most species. Additional gear added few new species. Resampling confirmed these results. When researchers and managers initiate sampling on a new stream or river system, they do not know how effective each gear type is and whether their sampling effort is adequate. Although the types and amount of gear may be different for other studies, systems, and research questions, the five‐step process described here for making sampling decisions and evaluating sampling efficiency can be applied widely to any system to restore, manage, and conserve aquatic ecosystems. It is believed that incorporating this gear‐evaluation process into a wide variety of studies and ecosystems will increase rigour within and across aquatic biodiversity studies. Copyright © 2013 John Wiley & Sons, Ltd.